Malaysian Islamic bankers' perceptions of al-Qard al-Hasan - Mohd Ariffin, Noraini; Adnan, Muhammad Akhyar (International Association for Islamic Economics, 2011)
This paper studies the perceptions of Islamic bankers in Malaysia about the concept and operation of al-qard al-hasan. It is based on a questionnaire survey of 13 full-fledged Islamic banks in Malaysia to which there was a 46.9% response rate. The findings show that the Islamic bankers in Malaysia are familiar with al-qard al-hasan and that they agree that Islamic banks should offer al-qard al-hasan in order to enhance corporate social responsibility and to help needy people. However, due to zero profit elements and high risk, it is very difficult to offer al-qard al-hasan. The paper concludes that Islamic banks need to diversify the products and services they offer so as to balance their orientation to profit with a stronger commitment to products and services, like al-qard al-hasan that will demonstrate their status as Islamic entities and improve their public image through good corporate social responsibility. However, offering zero profit and high risk services entails improvements in policy and operational guidelines.